Beifang International Education delegation visits UMPSA - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 17 April 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received a courtesy visit from a delegation from Beifang International Education, Tang Chinese Education Malaysia/China and BELIA MAHIR.